FOREIGN EXPERIENCE IN FINANCING INVESTMENT PROJECTS AND ITS FEATURES (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the theoretical foundations of investment project financing and the experience of foreign countries. During the study, the main models of investment project financing were studied - corporate financing, project finance and public-private partnership (PPP) mechanisms. Also, practical experiences were considered on the example of Great Britain, the USA, China and Germany, and their specific features were analyzed. As a result of the analysis, it was determined that risk sharing, the use of long-term financial resources and the development of public-private sector cooperation are of great importance in the effective financing of investment projects. At the end of the article, practical proposals and recommendations for the national economy in this area were developed.